Enhanced Photocatalytic Activity of Silver Doped ZnO for Degradation of Rhodamine 6G - Siva Kumar, S.; Ranga Rao, V.; Nageswara Rao, G. (Asian Journal of Chemistry, 2012)
Rhodamine 6G is a basic dye used to dye wool, cotton, silk and paper where brilliant shades of fluorescent effects are required. But the release of this complex dye and its products in to the environment is hazardous. Hence the photocatalytic degradation of rhodamine 6G in aqueous solution was studied under visible light irradiation using ZnO and Ag doped ZnO. ZnO was doped with Ag of varying concentrations such as 0.5, 1.0, 1.5 atom percentages by liquid impregnation method in order to improve its photocatalytic activity and the samples were calcined at various temperatures for 2 h. The catalyst was characterized by XRD and SEM. Band gaps of ZnO and silver doped ZnO were calculated from UV-visible diffuse reflectance spectroscopic studies. The photocatalytic activity of ZnO was found to be enhanced by Ag doping. The dye degradation was investigated at different initial dye concentrations and photocatalyst doses.